Pengaruh Pemotongan Umbi Bawang Merah (Allium cepa) dan Konsentrasi Atonik terhadap Pertumbuhan dan Hasil Bawang Merah (Allium cepa) - Miftahul Riska Jones; Helti Andraini; Frederika Eliesti (Pendidikan Biologi FKIP UMMY, 2021)
Shallots (Allium cepa) are one of the most important horticultural commodities in Indonesia. The need for shallots continues to increase, but the productivity of shallots does not increase. The purpose of this study was to determine the appropriate cutting height of shallot bulbs, to determine the appropriate concentration of atonic immersion and to determine the interaction of the two on the growth and yield of shallots (Allium cepa). This research was conducted in a paddy field located in Jorong Parumahan, Nagari Paninggahan, Junjung Sirih District, Solok Regency from March to June 2021. This study used a factorial randomized block design (RAKF) with 2 factors, namely the 1st factor cutting tubers with 3 level: M1 (without cutting), M2 (cutting 1/4 part), M3 (cutting 1/3 part), 2nd factor with 4 levels: A1 (without soaking), A2 (soaking 1.0 ml/l) , A3 (2.0 ml/l immersion), A4 (3.0 ml/l immersion). Parameters observed were the emergence of the first shoots, plant height, number of leaves, number of tillers, age of harvest, number of tubers/clump, weight of tuber/clump, production weight/ha. The results showed that there was no interaction between cutting and soaking at several atonic concentrations, nor a significant effect on both, but the best treatment on A3M3 (cutting tubers 1/3 part and soaking 3.0 ml/l) had a good effect on: the appearance of the first shoots is 7.16 (days), plant height is 24.07 (cm), the number of leaves is 13.5 (strands), the number of tillers is 13.05 (fruit), tuber weight / clump is 16.68 (grams) , and the production weight / ha is 3.82 (tons).